The dispute on hermeneutic philosophy - Błaszczyk, Marek (Hybris, 2020)
The paper presents a critical approach to Filozofia hermeneutyczna. Inspiracje, klasycy, radykalizacje by Włodzimierz Lorenc (Warszawa 2019). It aims to discuss the main theses presented in the dissertation and to invite to reflection focused on the specificity of hermeneutic philosophy, as well as its place in contemporary philosophy.